(untitled) (Italian Journal of Public Health, 2005)
Tracking health system performance is an issue that has commanded more and more attention within scientific and policy circles across the world in recent years. The monitoring of quality of care in both the US and Europe has risen on the national agenda to the point that major national efforts have been undertaken to measure and report on quality of health care delivery. The basic purpose behind national reporting efforts like the Osservasalute Report and the US National Healthcare Quality Report, is answering two main questions: what is the quality of care offered to the population? Are we getting better or worse quality of care out of our system? The analysis reported in the paper shows many similarities between the two reports. The growing need for clinically specific information on the performance of health care systems is at the heart of the mandate for these two reports. Even though there are differences between the reports in terms of the specific indicators chosen and the presentation structure and style, there are many similarities in terms of the condition areas tracked in the report and the findings regarding variability across Italy and the US in terms of the quality of care offered in different states or regions of each country. The two reports are similar in that their development teams at Observatory on Health in the Italian Regions and AHRQ continue to work with a broad group of stakeholders to ensure that the reports are used as a tool to improve quality.